The effect of non-genetic factors on the body weight performance of Brahman Indonesia cattle at BPTU-HPT Sembawa - Zulkarnaen, Mochammad Hafizh; Indrijani, Heni; Anang, Asep; Ramdani, Diky; Husnu, Ghoffar (Faculty of Animal Husbandry, Universitas Padjadjaran, 2025)
Brahman Indonesia cattle are a superior beef breed developed in Indonesia to increase national productivity, but their performance is influenced by various non-genetic factors. This study aimed to analyze the effect of these factors, specifically calf sex and dam parity, on the body weight performance of Brahman Indonesia cattle at BPTU-HPT Sembawa. Data from 2014-2023, consisting of 5,213 records (2,115 birth weight, 1,672 weaning weight, and 1,426 yearling weight) from the progeny of 31 sires and 178 dams, were analyzed using the General Linear Model (GLM) and Duncan's Multiple Range Test. The results showed that both calf sex and dam parity had a very significant effect (P<0.0001) on all observed growth traits. Male calves were consistently heavier than female calves at all age stages, while dam parity exhibited a performance pattern that was lowest at the first parity and reached its peak at parities 3-6. These findings confirm the importance of correcting for non-genetic factors in selection programs to improve the accuracy of genetic evaluation for Brahman Indonesia cattle breeding stock.